Highly potent and selective NaV1.7 inhibitors for use as intravenous agents and chemical probes. Issue 21 (1st November 2017) - Storer, R. Ian; Pike, Andy; Swain, Nigel A.; Alexandrou, Aristos J.; Bechle, Bruce M.; Blakemore, David C.; Brown, Alan D.; Castle, Neil A.; Corbett, Matthew S.; Flanagan, Neil J.; Fengas, David; Johnson, M. Scott; et al.
Graphical abstract: Abstract: The discovery and selection of a highly potent and selective NaV 1.7 inhibitor PF-06456384, designed specifically for intravenous infusion, is disclosed. Extensive in vitro pharmacology and ADME profiling followed by in vivo preclinical PK and efficacy model data are discussed. A proposed protein–ligand binding mode for this compound is also provided to rationalise the high levels of potency and selectivity over inhibition of related sodium channels. To further support the proposed binding mode, potent conjugates are described which illustrate the potential for development of chemical probes to enable further target evaluation.